KEWENANGAN PENGADILAN TATA USAHA NEGARA (PTUN) DAN PENGADILAN PAJAK DALAM SENGKETA ADMINISTRASI PERPAJAKAN - Suseno, Bambang (Jurnal HUKUM BISNIS, 2026)
The taxation sector plays a strategic and vital role as the main source of state revenue, serving as a cornerstone for financing national development. However, the interaction between taxpayers and the tax authorities (fiskus) often gives rise to tax disputes due to differences in interpretation and implementation of tax regulations. To address these disputes, the government established a special judicial body through the Tax Court Law, which grants the Tax Court exclusive authority to examine and adjudicate tax cases. The enactment of this law has led to the assumption that all tax-related disputes must be settled solely within the Tax Court’s jurisdiction. Nevertheless, in practice, there remain instances where tax cases are filed with other judicial institutions, particularly the State Administrative Court (PTUN). This situation creates jurisdictional ambiguity and legal debate over the boundaries of authority between the Tax Court and PTUN, especially in cases involving Tax Assessment Letters (Surat Ketetapan Pajak/SKP) and objection decisions issued by the tax authorities. This study employs a normative legal research method with statutory and conceptual approaches to analyze the distribution of authority between these judicial institutions. The research aims to provide clarity on jurisdictional limits, ensure legal certainty in resolving tax disputes, and strengthen the institutional framework of tax justice in Indonesia. Keywords: authority, State Administrative Court, Tax Court, Tax Assessment Letter (SKP)